(untitled) (Eurasian Research Bulletin, 2025)
This study investigates the effects of argon ion bombardment on the photoelectric properties of a CdTe-SiO2-Si heterostructure. The research focuses on understanding the mechanisms of photo-electromotive force (photo-EMF) generation in cadmium telluride (CdTe) films, especially the inversion of photo-EMF polarity depending on the wavelength of the incident light. Films deposited at substrate temperatures between 250°C and 300°C demonstrated varying photovoltaic properties across different depths, which were influenced by the deposition angle and film thickness. Through spectral analysis, the study identified three types of samples based on their photo-EMF polarity behavior. The first type consistently showed A-polarity, the second exhibited B-polarity, and the third type displayed polarity inversion depending on the wavelength and illumination direction. Ion bombardment further modified the films’ characteristics by reducing thickness and altering conductivity, leading to significant changes in their photovoltaic behavior. The results suggest that the photo-EMF generation mechanisms are depth-dependent, with different regions of the film contributing to the overall photovoltaic response. These findings provide valuable insights into the layer-by-layer localization of photo-EMF generation mechanisms in CdTe films and demonstrate the potential of ion bombardment as a method to tune the photovoltaic properties of semiconductor heterostructures